La Foncière Chênelet : un modèle d’écoconstruction ambitieux pour le logement social, au risque de son architecture - Amélie Flamand; Lucie Gallet; Rémi Laporte (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The recent claim by an atypical project owner of a strong commitment to environmental issues appears to exhibit an alternative response to the traditional methods applied to social housing. In this article, we will study the case of Foncière Chênelet, a social landlord which describes itself as a societal project developer that pursues a holistic approach to the issues of sustainability in the sector. We will examine how this positioning takes shape in the operational field, and explore its impact on the architectural, urban and landscape forms, as well as on building-related professions and ways of living. We will also focus on the housing model developed by Foncière Chênelet, and in particular on one specific project that illustrates this approach.